(-3xy-7y)+[4x-3(xy+y-2x)],其中xy=-2,x-y=3,先化简,再求值.
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/02 21:53:46
(-3xy-7y)+[4x-3(xy+y-2x)],其中xy=-2,x-y=3,先化简,再求值.(-3xy-7y)+[4x-3(xy+y-2x)],其中xy=-2,x-y=3,先化简,再求值.(-3x
(-3xy-7y)+[4x-3(xy+y-2x)],其中xy=-2,x-y=3,先化简,再求值.
(-3xy-7y)+[4x-3(xy+y-2x)],其中xy=-2,x-y=3,先化简,再求值.
(-3xy-7y)+[4x-3(xy+y-2x)],其中xy=-2,x-y=3,先化简,再求值.
(-3xy-7y)+[4x-3(xy+y-2x)],
=-3xy-7y+4x-3xy-3y+6x
=-6xy+10x-10y
=-6xy+10(x-y) xy=-2,x-y=3
=-6×(-2)+10×3
=18+30
=48
x^3y(-4y)^2+(-7xy)^2*(-xy)-5xy^3*(-3x)^2
【x(xy-xy)-y(x-xy)】÷3xy
-x-3xy+y
已知1/x-1/y=2,求3x+7xy-3y/2x-3xy-2y答案是1/x-1/y=2(y-x)/xy=2 得:x-y=-2xy(3x+7xy-3y)/(2x-3xy-2y)=[3(x-y)+7xy]/[2(x-y)-3xy]=(-6xy+7xy)/(-4xy-3xy)=xy/(-7xy)=-1/7 谁能帮我解释一下=[3(x-y)+7xy]/[2(x-y)-3xy]=(-6xy+7xy)/(-4xy-3xy) 是怎
(X-3xy+4xy-y)-[-2x-2(xy-3/2xy)-y]+6xy的过程
xy-2{xy-[3x^2y-(4xy^2+0.5xy)]+4x^2y}+6xy^2
化简:3x^2-[5xy-(x^y-3xy)+4x^2y-8xy]
因式分解:12xy^2(y-x)+xy^3(x-y)+4x^2y(x-y)
3xy+xy+3+4xy-7化简,已知x=5,y=6
求(3x^+y^-5xy)-【2x^-(-4xy-y^+7x^)】=?
求(3x^+y^-5xy)-【2x^-(-4xy-y^+7x^)】=?
(-3x^y+2xy)-( )=4x^+xy
5x^3y*(-3y)^2+(-6xy)^2*(-xy)+xy^3*(-4x^2)
当x-y=2xy时,求4x-3xy-4y/xy
XY(XY+3)+(XY+4)+4(X+Y+1)-(X+Y+2)
3(x平方y+xy)-4(xy-2x平方y)-(xy)
3(x^2y+xy)-4(xy-2x^2y)-(-xy)
x-y=3,xy=5,求代数式(7xy+4x-7y)+(6x-3xy)-(3y+4xy)的值快